2016
DOI: 10.1080/14760584.2016.1182869
|View full text |Cite
|
Sign up to set email alerts
|

Dry influenza vaccines: towards a stable, effective and convenient alternative to conventional parenteral influenza vaccination

Abstract: Cold-chain requirements, limited stockpiling potential and the lack of potent immune responses are major challenges of parenterally formulated influenza vaccines. Decreased cold chain dependence and stockpiling can be achieved if vaccines are formulated in a dry state using suitable excipients and drying technologies. Furthermore, having the vaccine in a dry state enables the development of non-parenteral patient friendly dosage forms: microneedles for transdermal administration, tablets for oral administratio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 20 publications
(15 citation statements)
references
References 110 publications
(188 reference statements)
0
15
0
Order By: Relevance
“…To our knowledge, this is the first study to show that an effective Advax-adjuvanted dry powder influenza vaccine formulation with full retention of biological activity of the WIV antigen and the Advax adjuvant can be prepared by SFD. Though both liquid and dry powder influenza vaccine formulations can be used for pulmonary administration, a dry powder formulation is preferable due to its long-term stability at ambient temperatures, which facilitates stockpiling [10,57,58]. In cases of an influenza pandemic, a stockpiled dry powder formulation would be readily available and easy to administer in mass vaccination campaigns.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…To our knowledge, this is the first study to show that an effective Advax-adjuvanted dry powder influenza vaccine formulation with full retention of biological activity of the WIV antigen and the Advax adjuvant can be prepared by SFD. Though both liquid and dry powder influenza vaccine formulations can be used for pulmonary administration, a dry powder formulation is preferable due to its long-term stability at ambient temperatures, which facilitates stockpiling [10,57,58]. In cases of an influenza pandemic, a stockpiled dry powder formulation would be readily available and easy to administer in mass vaccination campaigns.…”
Section: Discussionmentioning
confidence: 99%
“…administration for preventing influenza associated illness [8]. Pulmonary vaccines can be delivered as liquids or as dry powders [6,9,10]. In pre-clinical studies, pulmonary delivery of both liquid and dry powder influenza vaccine formulations has shown to induce mucosal as well as systemic immune responses [6,7,11,12].…”
Section: Introductionmentioning
confidence: 99%
“…For instance, decorating VLPs with variant specific surface proteins from Giardia lamblia has allowed to effectively induce, upon oral administration, immunoprotection against influenza and cancer in murine models [34]. The cases of the nasal influenza vaccine licensed for human use and the development of dried formulations to be administered by noninvasive routes illustrate the potential of mucosal vaccines to surpass the difficulties during their developmental path [35]. Moreover, other mucosal routes are acquiring special interest in vaccinology.…”
Section: Expert Opinionmentioning
confidence: 99%
“…However, it should be kept in mind that small antigen dose (typically less than 1 mg) can be administered via coated microneedles, due to the limited dimensions of microneedles shaft and tip -thick coatings are generally accompanied with a very low skin delivery efficacy because of a reduced sharpness of microneedle arrays (82,86). Composition of coating solution depends on the nature and type of antigen investigated and commonly includes viscosity enhancer (e.g., carboxymethylcellulose (CMC), methylcellulose) to achieve sufficient thickness of coating layer, stabilizing saccharide (e.g., trehalose, sucrose) to retain activity of antigen during drying/storage and surfactant (e.g., poloxamers) to decrease the surface tension and thus to assure uniform coating efficiency (95,96). Additionally, Choi and co-workers (97) observed that addition of viscosity enhancers was necessary to reduce the osmotic stress (caused by high concentrations of sugars) and to preserve activity of completely inactivated influenza virus during the microneedle coating.…”
Section: Types Of Microneedlesmentioning
confidence: 99%